Building Economic Intelligence in the Perspective of Islamic Values through a Family Education in Madura - Hadi, Saiful (KARSA Journal of Social and Islamic Culture, 2016)
Economic intelligence refered to here is the competence of individual in know-ledge acquisition about the world of business in the form of production, con-sumption, and distribution. Process model of building economic intelegence through of family education can be seen in Mr. Sudar family in Kaduara Timur Village, Pragaan Subdistrict, Sumenep Regency of Madura. Mr. Sudar works as mindreng and has three sons; the oldest son opens business digital printing, the second son opens the culinary business and pharmacies, and the third son works as mindreng. All three sons are very influenced by the daily behavior of father and mother at home when they were children. They received good advice and phrases embedded in their family, namely manossa coma dhÃ¢rma (men can only try, and God disposes), tÃ¡ atanÃ© tÃ¡ atanÃ¡ (no farming is no cooking), adhÃ¢ghÃ¢ng adhÃ¢ghing (be a trader in order you can consume meat). The consumtion patterns are tied by learning process that people can get successful if they have two prin-ciples: (1) jhÃ¢â€™ alapola, and (2) jhÃ¢â€™ akalpokal. Economic inteligence on aspect distribution implanted in a family environment in Mr. Sudar family that work is aimed at odiâ€™ samporna (perfect life), work is not only as the activities to fulfill a life need but also a blessing of life (bherkat tor slamet). Copyright (c) 2016 by KARSA. All right reservedÂ DOI: 10.19105/karsa.v24i2.891